2012
DOI: 10.1016/j.ajhg.2012.04.019
|View full text |Cite
|
Sign up to set email alerts
|

RAD21 Mutations Cause a Human Cohesinopathy

Abstract: The evolutionarily conserved cohesin complex was originally described for its role in regulating sister-chromatid cohesion during mitosis and meiosis. Cohesin and its regulatory proteins have been implicated in several human developmental disorders, including Cornelia de Lange (CdLS) and Roberts syndromes. Here we show that human mutations in the integral cohesin structural protein RAD21 result in a congenital phenotype consistent with a "cohesinopathy." Children with RAD21 mutations display growth retardation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
242
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(254 citation statements)
references
References 67 publications
7
242
2
3
Order By: Relevance
“…Notably, these individuals show a relatively mild phenotype compared with classic CdLS, particularly limb involvement and developmental delay. 11,12 Patients with mutations in HDAC8 have features suggestive of CdLS but with some atypical features including large anterior fontanel, hooded eyelids, broader nasal root and pleasant personality. 13 In this X-linked form of CdLS the hemizygous males are more severely affected.…”
Section: Can a Diagnosis Be Made Other Than Through A Genetic Test?mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, these individuals show a relatively mild phenotype compared with classic CdLS, particularly limb involvement and developmental delay. 11,12 Patients with mutations in HDAC8 have features suggestive of CdLS but with some atypical features including large anterior fontanel, hooded eyelids, broader nasal root and pleasant personality. 13 In this X-linked form of CdLS the hemizygous males are more severely affected.…”
Section: Can a Diagnosis Be Made Other Than Through A Genetic Test?mentioning
confidence: 99%
“…8,10 Mutations in RAD21 have been reported in eight patients with a CdLS phenotype: four whole-gene deletions, two missense, one inframe exonic deletion and one frameshift mutation. 11,12 Mutations in the HDAC8 gene account for~4% of mutations in individuals, including a phenotypically distinct subgroup of CdLS. 13,14 Reported mutations include missense (the most frequent type), chromosomal microdeletions or microduplications, nonsense and splice site.…”
Section: Mutational Spectrummentioning
confidence: 99%
“…With growing interest in RAD21, as the closely interrelated partner, it has been reported that STAG2 and RAD21 are involved in several meiosis stages and cooperate with a STAG3-specific complex to maintain sister chromatid cohesion during the diplotene stage of meiosis (Prieto et al, 2002). Further research shows that the mutations acting at the RAD21 interface with the other cohesin proteins, namely SA2 and SMC1A, impair cellular DNA damage response, and disrupt transcription (Deardorff et al, 2012). In addition, SA2 has direct contacts with specific regions of the C-terminal end of CTCF, and all other cohesin components are recruited through their interaction with SA2 (Xiao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Specifi cally, SUMOylation was found to antagonize the cohesin destabilizer Wapl because Wapl depletion alleviates the sister chromatid HR defect caused by SUMO target site mutation in Scc1 (Rad21) [ 13 ]. Interestingly, the SUMOylation sites overlap with SA protein binding sites, which are also found to be mutated in a developmental disorder related to Cornelia de Lange Syndrome (CdLS) , a type of cohesinopathy (diseases caused by dysregulation of cohesin and related factors) [ 38 ]. Although the exact function of SUMOylation remains unclear, these results provide important clues as to how cohesin is regulated under damage conditions to enable effi cient sister c hromatid HR .…”
Section: Cohesin Promotes Sister Chromatid Hr and Suppresses Nhej Andmentioning
confidence: 99%